Tourism Commodities, Cost, Comfort, and Communication: Shaping Tourist Perceptions and Revisit Decisions at Palabuhanratu - Chera Anggraeni; Muh Abdul Aziz; Alhidayatullah (PT. Maju Malaqbi Makkarana, 2026)
This study aims to examine the influence of tourism commodities, tourism costs, tourism comfort, and tourism communication on domestic tourists' perceptions and their impact on revisit decisions at Palabuhanratu Beach, Sukabumi Regency. This research employed a quantitative approach using an explanatory research design. The sample consisted of 150 domestic tourists selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed through Structural Equation Modeling (SEM) with IBM SPSS Statistics 26 and IBM SPSS AMOS 24. The findings reveal that tourism commodities, tourism costs, and tourism comfort have a positive and significant effect on domestic tourists' perceptions, while tourism communication does not significantly affect domestic tourists' perceptions. Furthermore, domestic tourists' perceptions, tourism costs, and tourism communication have a positive and significant effect on revisit decisions. In contrast, tourism commodities and tourism comfort do not directly influence revisit decisions. The findings indicate that domestic tourists' perceptions play a crucial role in encouraging revisit decisions. Therefore, destination managers should improve the quality of tourism commodities, enhance tourist comfort, establish appropriate tourism pricing, and strengthen tourism communication strategies to build positive perceptions and increase tourist loyalty through revisit decisions.